ANTI INFLAMMATORY ACTIVITY OF SILVER NANOPARTICLES SYNTHESISED USING INDIAN HERBS -A REVIEW - Thameemul Ansari.K.A, Mohamed; S., Rajeshkumar; A., K.Anjali (International Journal of Psychosocial Rehabilitation, 2020)
Aim: This study reviews the anti-inflammatory activity of Indian herbs using silver nanoparticles. Materials and Methods: Data and all other information are collected from highly rated articles. Articles are taken from various search engines like PubMed, Google Scholar, BioRXIV, Elsevier, and MedRXIV. The year in which the data collected were from was Jan 2010-May 2020, and the study was conducted in June 2020. Results: The review about the anti-inflammatory activity of silver nanoparticles synthesized using Indian herbs shows numerous health benefits of Indian herbs in the field of medicine. Herbs like turmeric, ashwagandha, peppermint, and Curcuma longa help to boost the immune system function and help clear off toxins from the body. It helps to fight against urinary tract infections, obesity, arthritis, stomach disorders, heart failure, and impotence. It is a potent diuretic good for eyes and liver. Conclusion: Silver nanoparticles have many benefits in various fields, especially in health care. It is used in many ways in health care, like for UV protection, topical ointments, creams, and nutraceuticals, and biomedically for cancer therapy, drug delivery, diagnosis, and cell imaging. Indian herbs can be used for future medicine development to get a good prognosis for various types of cancer and other diseases.